2020
DOI: 10.1097/gox.0000000000003143
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Multidisciplinary Craniofacial Care to Telehealth during the COVID-19 Pandemic: A Single Center Experience

Abstract: Summary: Craniofacial clinics are composed of multidisciplinary teams of providers to deliver coordinated and comprehensive patient care. The coronavirus disease of 2019 (COVID-19) pandemic has disrupted this model, as social distancing guidelines have precluded in-person patient appointments and forced clinics to reconsider their method of care delivery. The University of California, San Francisco, Craniofacial Center has continued to serve patients during this acute period, adopting a hybrid mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…9 Prior research by Badiee et al, cited that 87% of the patients and families surveyed somewhat or strongly agreed that they were satisfied with their video visits, and nearly all felt comfortable using the virtual service of the craniofacial center. 10 Results from our online survey produced mostly anticipated outcomes, with 72.3% of parents being overall satisfied, and supported the findings of the previous studies. However, answers from the present survey yielded an unexpected result, also.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…9 Prior research by Badiee et al, cited that 87% of the patients and families surveyed somewhat or strongly agreed that they were satisfied with their video visits, and nearly all felt comfortable using the virtual service of the craniofacial center. 10 Results from our online survey produced mostly anticipated outcomes, with 72.3% of parents being overall satisfied, and supported the findings of the previous studies. However, answers from the present survey yielded an unexpected result, also.…”
Section: Discussionsupporting
confidence: 88%
“… 9 Prior research by Badiee et al, cited that 87% of the patients and families surveyed somewhat or strongly agreed that they were satisfied with their video visits, and nearly all felt comfortable using the virtual service of the craniofacial center. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has forced a shift to virtual format across the full spectrum of healthcare services, and others have described telehealth adaptations for MDT or MDC previously for other clinical contexts aside from colorectal cancer [7][8][9][10][11]. In what is the closest example to the work in this study, Grenda et al reported how the Multidisciplinary Lung Cancer Clinic at the University of Pennsylvania was adapted to a telehealth format [8].…”
Section: Discussionmentioning
confidence: 80%
“…17 It facilitated remote care, increased geographic access, reduced viral transmission, decreased psychosocial burdens, 18 and lowered patient traffic in clinical settings. 19 Remote practices that used telemedicine also proved to reduce cost, time, and travel strain on patients and their families. 20 Telemedicine also facilitated interprofessional collaboration and dissemination of expertise beyond major medical centers.…”
Section: Telemedicinementioning
confidence: 99%